EFEKTIFITAS PELATIHAN TENTANG PENCEGAHAN SCABIES DAN MENINGKATKAN PERILAKU HIDUP BERSIH DAN SEHAT PADA SANTRI MENERAPKAN MODEL FOTOKIMIA DAN TRAFIC GAME HERBAL - Sri Herlina; Majida Ramadhan; Anita Puspa Widiyana; Dwi Praseyto, Hamdani; Sayidati Nabila; Wardah; Ahmad Asyari Fasya (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2024)
ABSTRACT The problem of students who live in dormitories often experience itching due to the transmission of scabies disease caused by the Sarcoptes scabiei mite, poor sanitation environments, such as hanging dirty clothes and bedding which serve as preferred living habitat other than in human skin. Scabies mites can survive 2-3 days in the external environment of the body, especially on fabrics such as clothes, towels, and mattresses. The personal hygiene of students and the habits of students do not apply Clean and Healthy Living Behavior, such as the habit of littering. Toilets are poorly maintained and do not wash their hands when consuming snacks; even allowing clogged drains can cause puddles at risk of falling due to slippery floors causing accidents for students, even though the management of the boarding school has given directions and appeals to students, but the application is still low. The method of implementing training activities is carried out by means of active interaction, active discussion, and role play with students and direct practice of waste treatment using a modified model of photochemical technology and a rapid sand filter. Increasing the understanding of students managerially using the herbal game traffic method approach is expected to be able to increase awareness and sensitivity in solving these problems. The results of the analysis of students' knowledge can understand that the cleanliness of clothes, towels, and tools can affect the transmission of scabies. The level of understanding of students is 0.43%. In PKM training activities, there are 98% of students who have increased their understanding of healthy and nutritious nutrition and can be developed in Islamic boarding schools as healthy snacks, while the practice of herbal games is still a model for problem recognition, and herbal solutions are said to be rarely applied by 40% to prevent scabies, both using herbal preparations and the application of clean and healthy living behaviors. Keywords: Santri, herbal game traffic, scabies, rapid sand filler, photochemistry